The study of potential of replacing pressed steel with fibre reinforced polyested for the water supply storage system [compact disc] - Mahaindran Kristnan, 1959- (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Sarjana Muda Kejuruteraan Awam) - Universiti Teknologi Malaysia, 2003